Preface - Paparazzo, Ernesto (Current Physical Chemistry, 2012)
The present issue marks the beginning of the second year of Current Physical Chemistry (CPC). Although the Journal is still in its infancy, I shall attempt both to draw up a balance of what it has offered so far, as well as to anticipate what it will offer to its readers in the near future and in the long term. In 2011 CPC has published separate feature articles, as well as series of articles grouped together to form a Special Issue concerned with a given topic. In either form of presentation, articles have equally undergone a peer-reviewing process involving at least two external referees, and have discussed experimental and/or theoretical physical chemistry studies of inorganic, organic and biological systems relevant to materials science, metallurgy, electrochemistry, nanotechnologies, medicine and geology. Moreover it has occasionally hosted articles dealing with the historical and philosophical foundations of Physical Chemistry. All the Members of the Editorial Board of CPC are active in various branches of Physical Chemistry, and recent entries now make it composed of scientists originating from all five continents, a combination which ensures a broad coverage of the scope of the Journal both in thematic and territorial terms. Over the past few years, the boundaries of Science (and Physical Chemistry is no exception) have impressively expanded. Such expansion arises not only from the “new” topics which are being studied, but also form the “new” countries (until recently usually referred to as “emerging” countries) where an ever-growing part of research is being carried out. Bentham Science and myself hope that authors from either party will find CPC a suitable forum to record salient phases of an ideal and much profitable challenge, to the benefit of the whole scientific community. As well as an advancement of our understanding of Physical Chemistry, the impressive rise of scientific research (and the attendant rise of competition) have produced a very negative side-effect on the literature - plagiarism- a threat which is the worst of all responses to the old imperative “publish or perish”. I think that plagiarism admits of no mitigation, because with ìt comes something which is even worse than “death” (of research): by setting the clock of scientific progress backwards, it in fact goes counter the “birth” of research. Bentham Science strive to curb this malicious practice by carefully checking the “originality” of each single article submitted prior to considering it for publication in one of their journals, and CPC is no exception. This is one of the essential steps needed to ensure that the quality of the articles published will soon add CPC to the Bentham journals which have already found a seat in the ISI-JCR list and gotten an impact factor, a goal which will prove beneficial to both the authors’ research records and the Journal's reputation. Mentioned in the following list are some new editorial initiatives which Bentham will offer to the readers of CPC. 1. As well as regular articles (either separate, or as part of a Special Issue), the Journal will consider the publication of another kind of contribution (referred to as “Letter to the Editor”), that is, comment articles which offer alternative views/interpretation of issues dealt with by articles previously appeared in CPC. These contributions will undergo the review evaluation by at least one external referee, and the author(s) of the article commented upon will be given the chance to offer an article in response to the comment. 2. The Journal will solicit articles from pre-eminent scientists who have made remarkable contributions to the field of Physical Chemistry. These articles will be published under the heading of a section called “Ground-Breaking Research.”.....